ANALYSIS OF THE RELATIONSHIP BETWEEN THE COMPETITIVE CAPABILITIES OF COMMODITY EXPORTS AND THE RENTIER ECONOMY FOR THE PERIOD (2004-2021) IN THE IRAQI ECONOMY - Jaafar Baqir Alloush; Bidaa Jawad Kazem (Scholars Digest Publishing, 2024)
The issue of competitiveness occupies broad interest in international economies, especially with the developments represented by globalization and global economic integration, as well as policies of openness and market liberalization. The concept of competitiveness goes beyond the state’s ability to produce goods and services that compete worldwide to the challenges that enable the state to produce goods and services and offer them in local and international markets. Thus, competitiveness is linked to export capabilities, the global trade climate, and the state’s ability to access global markets.